PENGEMBANGAN BAHAN AJAR E-BOOK KUMPULAN DONGENG DENGAN SOAL BERBASIS AKM PADA SISWA SEKOLAH DASAR - Aprillia, Mia; Prana Dwija Iswara; Dadan Djuanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop AKM-based e-book teaching materials for fairy tales designed to assist the Indonesian language learning process in fairy tale material. The background of this research is that teachers still experience limitations in developing digital teaching materials that are in line with student needs and AKM requirements. This research uses a Research and Development (R&D) approach with the ADDIE (Analyze, Design, Development, Implementation, and Evaluate) development model. The AKM-based fairy tale collection e-book teaching material was developed using Canva software as the basis for the e-book design, AI to help create images for each fairy tale, Quizizz to create questions for the final evaluation of each fairy tale, ME-QR online web to convert the Quizizz link into a barcode, and Heyzine online web to help convert the e-book pdf from Canva into a flipbook as a supporting display for the product. The results of validation by subject matter experts and media experts show that the AKM-based question collection e-book teaching materials are very feasible and usable. The implementation of these teaching materials helps teachers and students in the learning process. Evaluations and questionnaires reinforce the findings that these teaching materials are able to provide convenience and new experiences with the introduction of moral messages in them.